MODEL SUMBER DAN PENYEBAB REWORK PADA TAHAPAN PROYEK KONSTRUKSI - Chundawan, Erick; Alifen, Ratna S. (Magister Teknik Sipil Universitas Kristen Petra, 2014)
ABSTRACT: In construction, rework is unavoidable. Rework usually occurs due to mistake from workmanship cause by change, error and omission. Additional cost accruing from of rework on a construction project in Surabaya is around 5.7% from the total cost of project.In this research, questionnaires were distributed to contractors in Surabaya. Questionnaires were composed based on the construction phases, the sources and the causes of rework in order to design a model of rework on construction project. With the establishment of the sources and causes model of rework project managers can anticipate the occurrence of rework in accordance with the project construction phase.The research findings show that construction project in general, rework happens frequently in the phase of finishing activity in the construction phase, the sources of rework that must be considered for finishing activity is due to change order and followed by error that is caused by lack of leadership and communication. The highest intensity of the main indicators of the causes is inadequatecy of supervision and job planning.